2015
DOI: 10.1111/jvs.12335
|View full text |Cite
|
Sign up to set email alerts
|

Annual plant functional traits explain shrub facilitation in a desert community

Abstract: Question: For a desert where winter is the driest, harshest season we asked: does the effect of dominant shrubs (Bulnesia retama) on annual species depend on (1) the functional traits of the latter, (2) the season of the year, or (3) the activity of livestock?Location: A low-density goat farm in central-northern Monte Desert, Argentina. Methods:We estimated the effect of shrubs using a log response ratio based on annual species population sizes underneath shrub canopies and in open spaces. We collected density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 42 publications
5
33
0
Order By: Relevance
“…5b). These results are in line with our manipulative experiment and other studies and meta-analyses (Liancourt et al 2005, He et al 2012, Rolhauser and Pucheta 2016. They could indicate a greater relative importance of positive S shrub effects than that of negative ones on the distribution and persistence of less drought tolerant grasses in harsh environments.…”
Section: Discussionsupporting
confidence: 92%
“…5b). These results are in line with our manipulative experiment and other studies and meta-analyses (Liancourt et al 2005, He et al 2012, Rolhauser and Pucheta 2016. They could indicate a greater relative importance of positive S shrub effects than that of negative ones on the distribution and persistence of less drought tolerant grasses in harsh environments.…”
Section: Discussionsupporting
confidence: 92%
“…While other experimental studies have focused on shrub effects on herbs (e.g. Liczner, Sotomayor, Filazzola, & Lortie, ; Rolhauser & Pucheta, ) or short‐term seedling survival (Leiva, Mancilla‐Leytón, & Martín Vicente, ; Sthultz, Gehring, & Whitham, ), our data provide strong experimental evidence of the long‐term facilitative effect of shrubs on other woody species.…”
Section: Discussionsupporting
confidence: 57%
“…). Recent attempts to examine the interaction outcomes as a function of plant strategies have found that plants with acquisitive attributes such as high SLA and LA (Rolhauser & Pucheta ) or taller plants at maturity (Butterfield & Briggs ; Soliveres et al . ) are more liable to be involved in facilitative interactions.…”
Section: Discussionmentioning
confidence: 99%